PENGARUH PENGGUNAAN METODE DEMONSTRASI TERHADAP KOMPETENSI PROFESIONAL SISWA PADA MATA PELAJARAN MENGOLAH MAKANAN KONTINENTAL KELAS X DI SMK N 1 SINTUK TOBOH GADANG - Gustina, Gustina; Baidar, Baidar; Silfeni, Silfeni (Journal of Home Economics and Tourism, 2013)
This research start from the fact at school that it has 55 % the result of the study of the students in class x on Jasa Boga Competition in Subject Prosessing Continental Food are down of the KKM (7,5).This process make the hypothesis because of the proseces of the study still focus to the teacher and the studying process in teaching, the teacher also teacher also explain the material with conventional method. The purpose of this research to know the effect using demonstration method of Professsional Competition  students in their subject the proses of continental food in class x Jasa Boga department at SMK N 1 Sintuk Toboh Gadang in academic year 2012 / 2013. The kind of this research is quasi experiment research by using factorial planning one direction with all the population are students in class x Jasa Boga SMK N Sintuk Toboh Gadang. The sample is taken by using Total Sampling technique. The instrument is used test to estimate professional competition students are value form practice of questions test that given in the last research. The data analysis technique get thitung > ttabel =  (4,8 > 1,67) in clusion, using demonstration method give positive effect it’s means that in significant level 0,05 of professional competition students on subject how do the process continental food in class x at SMK N 1 Sintuk Toboh Gadang in academic year 2012 / 2013.   Kata kunci: Metode Demonstrasi, Kompetensi Profesional.